Preparation and Properties of Sintered Brick Based on Coal Gangue and Fly Ash - Sun, Peng; Sun, Daosheng; Wang, Aiguo; Ge, Wenbin; Liu, Xinlan (Asian Journal of Chemistry, 2014)
Coal gangue and fly ash were selected as raw materials to prepare building sintered brick. The influence of ratio of coal gangue and fly ash and sintering temperature on mineralogical composition, compressive strength, linear shrinkage and pore size distribution of building sintered brick were investigated. The results indicated that mineralogical compositions of sintered brick were mullite, quartz and b-cristobalite. With the ratio of coal gangue and fly ash decreased and sintering temperature increased, the compressive strength and linear shrinkage of sintered brick increased. For ratio of coal gangue and fly ash = 1:1, the sintered brick with compressive strength of 63.88 MPa, linear shrinkage of 8.84 %, porosity of 15.28 % and average pore diameter of 203.9 nm was prepared at 1250 ºC and the porosity and average pore diameter reduced by 42.7 and 28.2 % with the temperature increased from 1050 to 1250 ºC, respectively.